Religiousity of Barus Community Central Tapanuli (A Study of the History and Influence of Tugu Nusantara Titik Nol in Barus) - Muhamad Burhanuddin (Universitas Islam Negeri Alauddin, 2022)
The zero point of Islam in the Barus archipelago is the beginning of a renewal of Islamic history in Indonesia. Many expert and researchers are agree and disagreement of the existence of Barus as the entrance of Islam in the archipelago. This study examines two formulations of the problem first the history of the development of Barus as the zero point of Islam in the archipelago. Second the extent of the role of the Islamic zero point monument in the archipelago for the development of Barus. The method in this studying literature with descriptive critical analysis of the history of Barus and field facts.The results of this study first Barus community had original beliefs in the form of Animism, Dynamism, and Parmalim. The existence of a port in Barus became the gateway to the entry of Islam, Hinduism, Buddhism, and Chistianity. Second the existence of the Zero Point Monument in Barus brings changes to the Barus Community starting from the care of historical sites, increased research in Barus, and increased tourists.